The impact of splinting mobile mandibular incisors on Oral Health‐Related Quality of Life—Preliminary observations from a randomized clinical trial. (17th March 2021) - Sonnenschein, Sarah K.; Ziegler, Philipp; Ciardo, Antonio; Ruetters, Maurice; Krisam, Johannes; Kim, Ti‐Sun
Abstract: Aim: To compare the Oral Health‐Related Quality of Life (OHRQoL) of patients with mobile mandibular incisors before and after full‐mouth disinfection (FMD) with and without splinting. Material and methods: Thirty‐four periodontitis patients with ≥1 mobile mandibular incisor (degree II/III) were randomly allocated to the test or control group. All patients received FMD and the test group additional splinting of teeth 33–43. OHRQoL was assessed before (BL) and 3 months after FMD (RE) using the Oral Health Impact Profile (OHIP)‐14. Data were compared within and between the groups (Wilcoxon test/Mann–Whitney U test). Results: Twenty‐eight patients (13 test group/15 control group) were re‐evaluated. FMD led to a reduction of the mean probing pocket depth (PPD; in mm) (test group: BL‐PPD 3.89 ± 1.03, RE‐PPD 2.82 ± 0.53; control group: BL‐PPD 3.58 ± 0.66, RE‐PPD 2.77 ± 0.59; each p  ≤ .001), the mean clinical attachment level (CAL; in mm) (test group: BL‐CAL 5.22 ± 1.38, RE‐CAL 4.79 ± 0.85; control group: BL‐CAL 4.58 ± 1.10, RE‐CAL 4.41 ± 0.96; each p  ≤ .05), and the mean OHIP‐14 summary scores (test group: BL‐OHIP 21.7 ± 11.06, RE‐OHIP 9.9 ± 8.96, p  = .0046; control group: BL‐OHIP 16.8 ± 8.27, RE‐OHIP 11.7 ± 8.55; p  = .0217). The reduction of the OHIP‐G14 scores was considerably higher in the test group but statistically not significant ( p  = .080). Conclusions: The results show a positive impact of non‐surgical periodontal treatment on OHRQoL and a possible tendency for further improvement by splinting mobile mandibular incisors.